#TITLE_ALTERNATIVE# - NATASIA (NIM : 13205010); Pembimbing : Dr. Achmad Munir, DITHA
Planar reflector antenna consists of two main components which are the antenna feed and the planar reflector itself. In this final project, the research is focused on the planar reflector which is built from periodically printed microstrip patches on the dielectric substrate and the ground plane. The design of planar reflector is based on the structure of artificial magnetic conductor (AMC). AMC, also known as high impedance surface (HIS), is one of artificial materials that behave like a perfect magnetic conducting (PMC) material which will give a zero degrees reflection phase shift to the incident waves. The structure of AMC has been modified by removing the solid conductor that connects the patch and ground plane which is called via. At the first step, investigation of the modified AMC surface is conducted by analyzing the characteristic of its unit cell. Some parameter designs such as the size, thickness, and property of material are investigated intensively. The investigation is continued by composing the planar reflector from periodically arrangement of unit cell and analyzing its performance with the illumination from an antenna feed namely pyramidal horn. These investigation and design process are done with 3D-simulator within S-Band frequency range from 2 Ã‚Â– 4 GHz. The design of planar reflector for working in S-Band is realized as a prototype to see its performances such as the VSWR, radiation pattern, and gain. These results will be used to validate the simulation results. Results from the research will give basic and feasible information to design a planar microstrip reflector antenna based on AMC for practical application on S-Band.